The Implementation of Dictogloss Technique In Improving Listening Comprehension of The Eighth-Grade Students of MTS Negeri 2 Parigi - Nurdia, Nurdia; Aminah, Aminah; Desrin Lebagi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The purpose of this study is to find out how well the Dictogloss technique helps class VIII students at MTs Negeri 2 Parigi improve their listening comprehension. The Dictogloss technique's efficacy in enhancing listening comprehension is the primary research question. This quantitative study employed a quasi-experimental research design with a pre-test, treatment, and post-test with two classes designated as the experimental class and control class. The member in this test was eighth grade understudies. The researcher used a pretest and a posttest to gather data. SPSS version 23 was used to analyze the data that were collected. Students in the experimental class scored 53.83 higher on the posttest on average than students in the control class (42.22). The independence sample t-test revealed that the sig (2 tailed) value (0.000) was less than 0.05. This demonstrates the acceptance of the alternative hypothesis. Subsequently, the analyst presumed that the Dictogloss technique is successful in further developing the listening understanding of class VIII understudies at MTs Negeri 2 Parigi.